. Increasing the efficiency of casting manufacture in small-scale and single-unit production - M. A. Sadokha; S. L. Rovin (Литьë и металлургия, 2020)
Foundry is a multidisciplinary industry of engineering, providing cast blanks from various metals and alloys. The seriality of production has a great impact on the efficiency and quality of the castings being received. Single-unit and small-scale foundry production is an important part of modern engineering. Structural analysis of casting technology is presented in the article, individual technological changes are considered both in terms of impact on the efficiency of casting, and in terms of high quality assurance at minimal cost. Taking into account the need for a single-unit and small-scale casting in the fl xibility of the processes, schemes of organization of technological preparation of production and technological equipment are proposed. Examples of the equipment used are given.